Comparative Study of 2D and 3D Optical Imaging Systems: Laparoendoscopic Single-Site Surgery in an Ex Vivo Model. (December 2017) - Vilaça, Jaime; Pinto, José Pedro; Fernandes, Sandra; Costa, Patrício; Pinto, Jorge Correia; Leão, Pedro
Background . Usually laparoscopy is performed by means of a 2-dimensional (2D) image system and multiport approach. To overcome the lack of depth perception, new 3-dimensional (3D) systems are arising with the added advantage of providing stereoscopic vision. To further reduce surgery-related trauma, there are new minimally invasive surgical techniques being developed, such as LESS (laparoendoscopic single-site) surgery. The aim of this study was to compare 2D and 3D laparoscopic systems in LESS surgical procedures. Materials and Methods . All participants were selected from different levels of experience in laparoscopic surgery—10 novices, 7 intermediates, and 10 experts were included. None of the participants had had previous experience in LESS surgery. Participants were chosen randomly to begin their experience with either the 2D or 3D laparoscopic system. The exercise consisted of performing an ex vivo pork cholecystectomy through a SILS port with the assistance of a fixed distance laparoscope. Errors, time, and participants' preference were recorded. Statistical analysis of time and errors between groups was conducted with a Student's t test (using independent samples) and the Mann-Whitney test. Results . In all 3 groups, the average time with the 2D system was significantly reduced after having used the 3D system ( P < .05). In the postexercise questionnaire, two thirds of participants showed a preference for using the 3D system. Conclusion . This study suggests that the 3D system may improve the learning curve and that learning from the 3D system is transferable to the 2D environment. Additionally, the majority of participants prefer 3D equipment.